Inter-species Competition Analysis Between Native Lowland Forest Trees to Optimize Land Rehabilitation Management in Bedegung Biodiversity Park, South Sumatra, Indonesia - Budiman, Mokhamad Asyief Khasan; Oue, Hiroki; Afandy, Andy; Al Anshori, Zakaria; Mulyana, Dadan; Kamsari (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Effective CO2 sequestration (SC) in rehabilitated tropical forest depends heavily on species performance and competition dynamics. This study evaluates SC potential and interspecific competition of native lowland forest tree species in Bedegung Biodiversity Park, South Sumatra, Indonesia―an area rehabilitated since 2014 through collaboration between the South Sumatra Provincial Environmental Service, National Gas Company (PGN), and IPB University. Despite the rehabilitation efforts, early planting did not consider the planting distances (Lij), impacting tree density (Dx) and individual competition index (CIi)―factors directly influencing SC. From 2020 to 2023, monitoring of tree diameter, height, and Lij data collected within a 60 × 20 m permanent plot revealed a decline in Dx from 900 ind ha–1 in 2020 to 725 ind ha–1 in 2023, primarily due increased competition. The site’s average SC reached 69.91 tCO2 ha–1 y–1, lower than mature tropical forests due to stand age. Among all species, Bayur (Pterospermum javanicum) exhibited superior SC performance, sequestering 10.02 ± 6.98 tCO2 ind–1 y–1―well above the mean―and showing increased resilience, indicaed by 1/CIi from 0.62 to 4.38. These results highlight Bayur’s exceptional role in SC under competitive pressure. For enhanced SC outcomes, management interventions such as thinning, fertilization, remove the weeds, and removing dead trees are urgently recommended. Prioritizing species with high SC potential and adaptive performance, like Bayur, is essential for optimizing carbon gains in forest rehabilitation programs.